Understanding consumers' reactance of online personalized advertising: A new scheme of rational choice from a perspective of negative effects. (February 2019) - Chen, Qi; Feng, Yuqiang; Liu, Luning; Tian, Xianyun
Highlights: Rational choice factors are reconstructed from a negative-effect perspective in the OPA context. Ownership affection fosters perceived cost of non-personalization and privacy concerns. Privacy concerns and opportunity cost increase with vulnerability affection. The impacts of ownership and vulnerability on reactance are mediated by rational choice factors. Abstract: Consumer reactance appears to be a major inhibiting result in the personalization paradox of online personalized advertising. The objective of this study is to uncover consumer reactance of online personalized advertising. We identify the rational choice factors rooted in the rational choice theory from a negative-effect perspective and examine their impacts on consumer reactance with consideration of affective factors. Our results confirm that three rational choice factors from a negative-effect perspective have significant impacts on consumer reactance, and affective factors such as ownership and vulnerability are dominant determinants of these rational choice factors. The effects of these affective factors on consumer reactance can be mediated by individual rational choice factors. The findings provide a new perspective on the paradox phenomenon and offer online personalized advertising providers new approaches to improving their performance.